The multifaceted functions of SPC25 in cancer: from molecular pathways to targeted therapy - Jin, Yigang; Chen, Minjie; Chen, Fei; Gao, Zhaofeng; Li, Xiaoping; Hu, Lingyu; Cai, Dandan; Zhao, Siqi; Song, Zhengwei (Frontiers in Medicine, 2025)
Spindle Pole Body Component 25 (SPC25), a critical component of the NDC80 kinetochore complex, plays an essential role in maintaining chromosomal stability during mitosis. Recent studies have revealed its aberrant expression in various cancers, highlighting its potential as both a diagnostic biomarker and a therapeutic target. This review provides a comprehensive analysis of the molecular mechanisms underlying SPC25’s involvement in tumorigenesis, including its regulation of cell cycle progression and interaction with key oncogenic pathways. Furthermore, we discuss its prognostic significance across different cancer types and its potential impact on therapy resistance. The emerging evidence underscores SPC25’s multifaceted role in cancer biology, offering novel insights into its clinical applications. We conclude by exploring future research directions, emphasizing the need for in-depth studies to unravel the precise molecular functions of SPC25 and its therapeutic potential in cancer treatment.